The Effect of Learning Style on Students’ Learning Performance During the Covid-19 Pandemic - Albeta, Sri Wilda; Haryati, Sri; Futra, Dedi; Aisyah, Riri; Siregar, Anggi Desviana (Jurnal Tadris Kimiya, 2021)
The research aims to determine the effect of learning style on students’ performance through online learning during the Covid-19 pandemic. The subjects of study are 269 chemistry education students at three universities in Indonesia. The data collection of learning style uses a Likert scale questionnaire, and learning performance is obtained from students’ grade point average. In this research, students’ learning style was divided into visual, auditorial, and kinesthetic. Data were analyzed using descriptive statistics with linear regression and ANOVA tests. The learning styles positively affect student learning performance by 4.7%, while 95.3% of other factors are not examined in this study. The learning performance of students with auditory is higher than visual and kinesthetic learning styles. Based on the inferential analysis, there is no significant difference in student learning performance based on student learning styles. Therefore, students with different learning styles have the same learning performance in online learning.